Emotions in Scottish Protestant Public Worship, 1560-1638 - Hood, Nathan C. J. (Edinburgh University Press, 2025)
Studies the emotional culture of corporate religious rituals in post-Reformation ScotlandAnalyses the role of emotion in early modern Scottish Protestant public worshipApplies methods and insights from the history of emotions disciplineEstablishes that religious conversion was at the heart of congregational worshipDiscusses the medieval, secular and transnational influences on Scottish ProtestantismHighlights how debates over emotion influenced the politics of seventeenth century ScotlandThis book explores the affective dimension of Scottish Protestant public worship in early modern Scotland. It examines how the intensely emotional character of Scottish Puritan or godly piety was reflective of the emotional norms many Scots had to navigate in congregational worship following the Protestant Reformation. Using historiographical approaches developed within the history of emotions discipline, the book argues that in corporate rituals such as prayer, preaching, public repentance, fasting and the Lord's Supper, Scottish Protestants were expected to experience and express a variety of feelings that were associated with the cycle of conversion. These prescribed emotions were seen as integral to the efficacy of the liturgy, playing a vital role in the individual's, community's and nation's encounter with God. The book argues that these standards of emotion were informed by medieval, secular and protestant sources and new perspectives emerge on their profound impact upon the major political events that shaped seventeenth century Scotland